Pure silica-supported transition metal catalysts for the non-oxidative dehydrogenation of ethane: confinement effects on the stability. Issue 17 (30th March 2022) - De, Sudipta; Aguilar-Tapia, Antonio; Ould-Chikh, Samy; Zitolo, Andrea; Hazemann, Jean-Louis; Shterk, Genrikh; Ramirez, Adrian; Gascon, Jorge
Abstract : All-silica MFI zeolite was used as a support for the synthesis of promoter-free robust transition metal catalysts. Effects of different physical parameters and catalyst deactivation mechanism were studied for the ethane dehydrogenation reaction. Abstract : Designing robust catalysts for high-temperature applications has always been a critical task for chemical industries. As an example, the non-oxidative dehydrogenation of alkanes is an important chemical process that requires thermally stable metal catalysts with high resistance to metal sintering. The main obstacle is to maintain the high dispersion of the active metal centres under reaction and regeneration conditions. In an attempt to overcome this issue, here we use all-silica zeolite as a support to make nanometric and single-site metal catalysts with enhanced stability for the non-oxidative dehydrogenation of ethane. Preliminary screening of different metal catalysts suggests that Co has the highest intrinsic activity while Cr and V are highly stable against sintering and display a moderate activity. The high stability of Cr and V could be attributed to their high Gibbs energy of reduction under reaction conditions. Operando X-ray absorption spectroscopy revealed that Cr based catalysts remain as single-site monomeric species during the reaction, making it possible to increase the loading and therefore productivity. In the case of Co, we established the optimum parameters to achieve the highest activity by evaluating the effects of support, metal loading, promoter, and synthesis process.